Monitoring of Beach Seine Cathing Inner Ambon Bay - Tuapetel, Friesland; Silooy, Frentje Dusyan; Rizki, Rizki (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
Our research aims to determine the shift in the catch of beach seine according to the perception of fishermen, to determine the catch of beach seine from September to October 2021, and to compare the catch in the same month with different years. The method of collecting data is through interviews, observations, and literature studies, then the results are analyzed descriptively and presented in the form of tables and figures. The results of the interview show that the number of beach seine and their catches in TAD is decreasing (number and types of fish). The results of two months of observation in 2021 for 31 trips, found only 15 species of fish with a total of 7257 individuals, and dominated by Stolephorus indicus 59.3%, Encrasicholina heteroloba 16.6% and Sardinella fimbriata 10.9%. The average length of S. indicus is 3.9 cm in the range of 2.1-6.7 cm and weighs 1.2 g (0.1-1.4 g). The results of beach seine monitoring in TAD showed a decrease in fish species by 29.41%, which is now dominated by S. indicus but with smaller body sizes, so it is necessary to conduct continuous research related to the ecobiology of the three types of fish that dominate the catch of the beach seine, as efforts to evaluate and monitor the use of fish resources in TAD sustainably and responsibly.